PENERAPAN METODE DEMONSTRASI PADA PEMBELAJARAN MENULIS TEKS PROSEDUR - Muhammad Ihsan As Sidiq; Muhamad Fathurohman Yudistira; Teti Sobari (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the curiosity of researchers regarding the process and results of improving students' skills in the procedure of writing text skills. What is the process and results of students' ability in writing procedure texts, namely by applying the demonstration method in the learning process? This study aims to determine the process and production results of procedural texts in class XI students using the demonstration method. The method used in this study is pre-experimental design. The sample used in this study is class XI Chemistry A, with a total of 25 students. Data collection techniques using the initial test (pretest) and the final test (posttest). Based on the results of the research the ability of students to write procedure texts before using the demonstration method obtained an average score (initial test) of 66.04 and after using the demonstration method obtained an average number (final test) 73.24. Our ability to write procedure texts increased to 7.2. so it can be concluded by using the demonstration method in class XI Chemistry A can improve students' ability in writing procedure texts.